A Formação Intelectual da Elite Sergipana (1822-1889) - Silva, Eugênia Andrade Vieira da (2004)
The aim of this paper is to analyze Sergipe´s intellectual formation during the empire period as well as to prove that the origin of that intellectuality was in that period and not in the republic. For that, it was observed the sending of Sergipanos students by the Province elite to educational Brazilian centers as well as European centers between 1822 and 1889. That time marks Sergipe´s identity as well as the national identity and also their performance as intellectuals in Sergipe, contributing, this way, to build up Sergipe´s intellectual profiles. To deeply analyze this intellectuality, it has been selected 400 (four hundred) names which have been recognized and legitimated by Sergipe´s society as intellectuals.